2010
DOI: 10.1002/art.27713
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic alterations of neurons that innervate osteoarthritic joints in rats

Abstract: Objective. Pain is a prominent feature of osteoarthritis (OA). To further understand the primary mechanisms of nociception in OA, we studied the expression of the phenotype markers calcitonin gene-related peptide (CGRP), isolectin B4 (IB4), and neurofilament 200 (NF200) in sensory neurons innervating the OA knee joint in rats.Methods Conclusion. These results indicate that MIAinduced OA causes an up-regulation of CGRP in different subpopulations of primary afferent neurons in DRG due to a phenotypic switch and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 47 publications
11
84
0
Order By: Relevance
“…CGRP-positive neuron areas were measured in the same IR cells randomly selected for cell counting (n = 5 rats for controls and the 4d MA; n = 4 rats for each of the other experimental groups). IR cells with visible nuclei were manually outlined using a computer mouse and the cross-sectional area was determined using the ImageJ version 1.37 (free access software) [29,30] . Cell areas were grouped into three categories: small ( !…”
Section: Cell Size Distributionmentioning
confidence: 99%
“…CGRP-positive neuron areas were measured in the same IR cells randomly selected for cell counting (n = 5 rats for controls and the 4d MA; n = 4 rats for each of the other experimental groups). IR cells with visible nuclei were manually outlined using a computer mouse and the cross-sectional area was determined using the ImageJ version 1.37 (free access software) [29,30] . Cell areas were grouped into three categories: small ( !…”
Section: Cell Size Distributionmentioning
confidence: 99%
“…The decrease in number of mechanoreceptors within ligaments, reported in animals [12] and humans [2,6,13], is presumably one of the underlying mechanisms. In addition, total number of knee joint aVerents decreases with aging [14] and OA changes [15,16] in rodents. Taken together, the decrease in the number of mechanoreceptors at least partially accounts for the age-related loss of joint innervation and progression of OA changes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results indicate that nociceptive inputs selectively remain in the PCL of OA knees, while the total innervation decreases. One possible reason for this Wnding is that OA and arthritic changes in knee cause an up-regulation of CGRP in rodent dorsal root ganglia [16,23], These Wndings will give new insights to the PCL issue in TKA and should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Animal model studies have demonstrated potent facilitation of the joint Group II afferents following induced joint inflammation [39] and induced monoarthritis [40,41]. Indirect evidence in patient populations may provide further support.…”
Section: Spinal Hyperexcitabilitymentioning
confidence: 94%